2022
DOI: 10.1098/rsbl.2022.0093
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that gecko setae are coated with an ordered nanometre-thin lipid film

Abstract: The fascinating adhesion of gecko to virtually any material has been related to surface interactions of myriads of spatula at the tips of gecko feet. Surprisingly, the molecular details of the surface chemistry of gecko adhesion are still largely unknown. Lipids have been identified within gecko adhesive pads. However, the location of the lipids, the extent to which spatula are coated with lipids, and how the lipids are structured are still open questions. Lipids can modulate adhesion properties and surface hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has been proposed that interactions between anionic intermediate filament keratins and positively charged CBPs produce resilient flexible corneous assemblies, disulphide bonding may also stabilize these structures. Protein-lipid interactions may also contribute to the pliability of these structures providing compliant properties to the setae improving their adhesion to irregular adhesive surfaces [131]. Nuclear Magnetic Resonance (NMR) spectroscopy also confirms the presence of lipid-keratin structures in the Gecko foot setae [132].…”
Section: Gecko Dry Adhesivementioning
confidence: 91%
“…It has been proposed that interactions between anionic intermediate filament keratins and positively charged CBPs produce resilient flexible corneous assemblies, disulphide bonding may also stabilize these structures. Protein-lipid interactions may also contribute to the pliability of these structures providing compliant properties to the setae improving their adhesion to irregular adhesive surfaces [131]. Nuclear Magnetic Resonance (NMR) spectroscopy also confirms the presence of lipid-keratin structures in the Gecko foot setae [132].…”
Section: Gecko Dry Adhesivementioning
confidence: 91%
“…These scales are underpinned by modified muscles, tendons, bones, and other tissues which function to fine‐tune the control of the scansors during locomotion, allowing for their correct placement onto—and removal from—the substratum (Russell, 1975, 2002; Russell & Gamble, 2019). The ultimate agents of adhesion are microfibrillar stalks (setae) arising from the “Oberhäutchen”—the outermost layer of the epidermis (Autumn, 2007; Hiller, 1968; Maderson, 1970), which generate adhesion via van der Waals forces (Autumn, 2006; Autumn & Peattie, 2002), probably acting in concert with electrostatic interactions (Izadi et al., 2014; Song et al., 2022) and surface chemistry (Rasmussen et al., 2022; Singla et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tree frogs similarly, but convergently, produce an adhesive liquid in their mucus glands to strengthen their attachment [ 17 , 18 ]. Geckos do not produce large amounts of tarsal secretion, but it has been shown that a nanometer thin lipid film covers the surface of their adhesive setae [ 19 ]. Especially in marine environments, other depletion mechanisms are found: Echinoderms, for example, secrete a two-phase secretion, where the first phase generates the adhesion and the second phase dissolves the first phase [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%